Transformations of Centre and Periphery for the Saami in Norway - Anderson, Myrdene (Anthropologica, 2022)
The Saami minority in each of the Fennoscandian nation states faces generalizable issues of articulation with national units. These issues also operate among and within national units. Historically, many Saami without a distinctive lifestyle such as reindeer breeding chose to assimilate into mainstream regional culture. As a consequence, Saami and non-Saami alike now tend to associate Saami culture with the reindeer-breeding minority within the Saami minority as a whole. Indeed, bureaucratic regulations and national measures impact differentially on various segments of the Saami population. This paper investigates repercussions for the Saami in North Norway who are simultaneously beneficiaries of national good intentions and victims of premeditated exploitation. All of this is exacerbated by the Saami minority's own faith in an eternal frontier and the policy makers' myth of a monolithic Saami culture.